Geochemistry and petrology of palaeocene coals from Spitzbergen — Part 2: Maturity variations and implications for local and regional burial models - Marshall, Chris; Uguna, Jacob.; Large, David J.; Meredith, Will; Jochmann, Malte; Friis, Bjarki; Vane, Chris; Spiro, Baruch F.; Snape, Colin E.; Orheim, Alv (Elsevier, 2015)
The Central Tertiary Basin is an uplifted part of the North Barents Shelf and should be an ideal location to understand the thermal history, maximum burial depth and overburden thickness in this petroleum-rich area. Efforts to quantify the thermal history of the region have been hampered by reports of hyper-thermal conditions, maturity gaps and maturity inversions in the Tertiary vitrinite reflectance (Ro) record. This has been attributed to thermal insulation effects, vitrinite reflectance due to bitumen impregnation and later Tertiary volcanism. Through the use of Ro, organic maturity parameters, 13C NMR and Rock–Eval pyrolysis, this study aims to explain the unusual maturity effects observed and the implications for burial models. Within single seams, Ro % ranges from 0.5 to 0.78 with increasingly bimodal distribution up-seam. Analysis of coal aromaticity and the results of Rock–Eval analysis confirm that maturity gaps and inversions only occur where the vitrinite reflectance has been suppressed by high bitumen content (300–400 mg/g coal). Samples with the lowest hydrogen index values (< 250 mg HC / TOC) provide the most accurate estimates of the vitrinite reflectance. Results indicate maximum burial temperatures of 120 °C in the basin centre and 100 °C at the basin margins with a hyper-thermal gradient of approximately 50 °C/km. This gradient implies a total overburden of 2 km of which 1 km has been lost. Maximum burial depth and total erosional sediment load to the Barents Shelf are therefore at the lower end of current estimates.